Enhanced Vigenere And Affine Ciphers Surrounded By Dual Genetic Crossover Mechanisms For Encrypting Color Images - Hamid EL BOURAKKADI; Hassan TABTI; Abdelhakim CHEMLAL; Mourad KATTASS; Abdellatif JARJAR; Abdelhamid BENAZZI (International Journal of Advanced Science and Computer Applications, 2025)
This paper introduces an enhanced technique for encrypting color images, surpassing the effectiveness of genetic crossover and substitution methods. The approach integrates dynamic random functions to bolster the integrity of the resulting vector, elevating temporal complexity to deter potential attacks. The enhancement entails amalgamating genetic crossover using two extensive pseudorandom replacement tables derived from established chaotic maps in cryptography. Following the controlled vectorization of the original image, our method commences with an initial genetic crossover inspired by DNA behavior at the pixel level. This process is followed by a confusion-diffusion lap, strengthening the relationship between encrypted pixels and their neighboring counterparts. The confusion-diffusion mechanism employs dynamic pseudorandom affine functions at the pixel level. Subsequently, a second genetic crossover operator is applied. Simulations conducted on various images with varying sizes and formats demonstrate the resilience of our approach against statistical and differential attacks.